A battle between titans? Rio Tinto and union recognition in Australia's iron ore industry. (February 2014) - Ellem, Bradon
In 2010, under pressure from newly unionised rail workers, the multinational mining company Rio Tinto agreed to bargain collectively with a union for the first time in its Australian iron ore operations since 1993. This re-unionisation of part of Rio Tinto was, for unionists, an impressive feat but, in itself, the campaign was familiar enough. What makes this empirically significant is the 'titanic' nature of the struggle in this vital sector. Its wider significance lies in a contribution to debate about 'successful' campaigns and in highlighting the importance of both national regulation and local context to these outcomes. More broadly still, this successful campaign poses questions about how we relate such episodes to ongoing failures elsewhere.